The Serum IL-6 Profile and Treg/Th17 Peripheral Cell Populations in Patients with Type 1 Diabetes - Monika Ryba-Stanisławowska; Maria Skrzypkowska; Jolanta Myśliwska; Małgorzata Myśliwiec (Hindawi Limited, 2013)
IL-6 is a pleiotropic cytokine involved in the regulation of the immune response, inflammation, and hematopoeisis. Its elevated levels are found in a range of autoimmune and chronic inflammatory diseases. IL-6 is also involved in regulation of the balance between two T cell subsets: Tregs and Th17, which have contradictory functions in the control of inflammation. The present study provides a quantitative analysis regarding the Th17/Treg cell balance in peripheral blood of children with type 1 diabetes and its association with serum IL-6 level.